%@Titre: Groupe Nord -- 2006 Soit $D=(2x+3)^2+(2x+3)(7x-2)$. \begin{myenumerate} \item Développer et réduire $D$. \item Factoriser $D$. \item Calculer $D$ pour $x=-4$. \item Résoudre l'équation $(2x+3)(9x+1)=0$. \end{myenumerate} %@Correction: \begin{myenumerate} \item\[\Eqalign{ D&=(2x+3)^2+(2x+3)(7x-2)\cr D&=(2x)^2+2\times2x\times3+3^2+2x\times7x+2x\times(-2)+3\times7x+3\times(-2)\cr D&=4x^2+12x+9+14x^2-4x+21x-6\cr D&=18x^2+29x+3\cr }\] \item\[\Eqalign{ D&=(2x+3)^2+(2x+3)(7x-2)\cr D&=(2x+3)(2x+3)+(2x+3)(7x-2)\cr D&=(2x+3)\times\left[(2x+3)+(7x-2)\right]\cr D&=(2x+3)\times\left[2x+3+7x-2\right]\cr D&=(2x+3)\times(9x+1)\cr }\] \item $D=18\times(-4)^2+29\times(-4)+3=18\times16-116+3=288-116+3=175$ \item C'est un produit nul donc \[\Eqalign{ 2x+3&=0&&\mbox{ou}&&9x+1&=0\cr 2x&=-3&&&&9x&=-1\cr x&=\frac{-3}2&&&&x&=\frac{-1}9\cr }\] Les solutions de l'équation sont $x=-\dfrac13$ et $x=-\dfrac19$. \end{myenumerate}